Pelaksanaan Kegiatan Diklat Aparatur Provinsi di BPSDM Provinsi Kalimantan Tengah oleh Bidang Pengembangan Kompetensi Manajerial - Siti Husnari; Abdul Gofur (Lembag, 2024)
Human resource development and management activities are very important as an effort to produce employees who are agile and competent in carrying out their job duties. This is the task of the Managerial Competency Development Division at the Central Kalimantan Human Resources Development Agency (BPSDM). This research aims to find out how the Provincial Apparatus Training Activities are implemented at BPSDM Central Kalimantan by the Managerial Competency Development Sector. The method used in this research is a qualitative method with descriptive research type through observation, interviews and documentation. The results of this research are that BPSDM Central Kalimantan Province in the Managerial field offers several training courses such as PKN II, PKA, PKP, LATSAR and DPRD Member Orientation which are designed in a structured and well-organized manner to ensure that participants acquire the relevant knowledge, skills and attitudes needed to carry out their duties. effectively and efficiently. This is interpreted from the existence of a clear curriculum, varied learning methods, competent teachers, objective evaluation and certification for training participants who have completed the learning.